KASIRKU Application Design with Mobile on Management Transaction, Stock and Sales Report - Rifan Rudiyanto, Arif; Fattah, Abdulloh; Mustagfirin, Mustagfirin (LPPM Universitas Sains dan Teknologi Komputer, 2025)
The development of technology in the retail world drives the need to create more efficient solutions in transaction management and stock of goods. Kasirku is a web-based cashier application designed for small and medium-sized stores. This application provides three main features, namely Transactions, Stock Items, and Sales Reports, with additional additional transaction features, discounts, taxes, add items, and QR scanners to simplify store operations. The Transaction feature assists users in recording sales efficiently, complete with options for adding items, applying discounts, and automatic tax calculation. The Stock Item feature allows store owners to monitor stock items in real-time, reducing the risk of out-of-stocks or recording errors. Sales Reports available in various formats, such as PDF or Excel, help store owners conduct more in-depth sales analysis. The development of the Kasirku application was conducted using the waterfall approach, which includes several steps: requirements analysis, design, implementation, and testing. The results of the testing process show that this application can increase efficiency in recording transactions, minimize errors in stock management, and produce precise reports. The QR Scan feature is proven to speed up the item input process when the store is busy, providing additional flexibility to users. This app has successfully become a reliable solution for store owners to manage their stores more easily and quickly.